PENDAMPINGAN METODE PEMERINGKATAN FAKTOR UNTUK MENINGKATKAN EFISIENSI LOKASI STRATEGIS DI UMKM SEBLAK CUANKI BANDUNG, KIRANA CIBITUNG - Astuti, Fitri Winda; Setyawati, Esty; Betty Deviyanti, Helga; Alchoiri, Rafly; Wiji Safitri (BEGAWI : Jurnal Pengabdian Kepada Masyarakat, 2025)
The selection of the right location plays a crucial role in the success of the MSME Seblak Cuanki Kirana in Pesona Gading Cibitung. Key factors such as accessibility, visibility, parking facilities, the surrounding environment, and the level of competition greatly impact operational performance and customer attraction. By using the factor rating method, the business location is evaluated based on a scale of values to determine the most optimal and profitable location. This approach helps MSME improve operational efficiency, enhance business visibility, and increase competitiveness in an increasingly competitive market. Furthermore, leveraging digital promotions through social media platforms like Instagram and Facebook has become an essential part of the marketing strategy to expand market reach and increase brand awareness. By combining the right location selection with digital marketing, MSMEs can increase sales, reduce operational costs, and build customer loyalty. The results of the assistance show that this method provides a clear and structured guide in planning a strategic business location while supporting the sustainability and development of Seblak Cuanki Kirana’s business. By optimizing the potential of the location and digital marketing strategy, MSMEs can expand its market, maintain competitiveness, and achieve sustainable business goals. This approach also emphasizes the importance of synergy between strategic location selection and marketing innovation in driving MSME growth in the competitive digital era.